7-Glutathione-pyrrole and 7-cysteine-pyrrole are potential carcinogenic metabolites of pyrrolizidine alkaloids. (3rd April 2017) - He, Xiaobo; Xia, Qingsu; Fu, Peter P.
ABSTRACT: Many pyrrolizidine alkaloids (PAs) are hepatotoxic, genotoxic, and carcinogenic phytochemicals. Metabolism of PAs in vivo generates four (±)-6, 7-dihydro-7-hydroxy-1-hydroxymethyl-5 H -pyrrolizine (DHP)-DNA adducts that have been proposed to be responsible for PA-induced liver tumor formation in rats. In this present study, we determined that the same set of DHP-DNA adducts was formed upon the incubation of 7-glutathione-DHP and 7-cysteine-DHP with cultured human hepatocarcinoma HepG2 cells. These results suggest that 7-glutathione-DHP and 7-cysteine-DHP are reactive metabolites of PAs that can bind to cellular DNA to form DHP-DNA adducts in HepG2 cells, and can potentially initiate liver tumor formation.